Cost efficient trust-based vehicle selection for platoon - Qiu, Hongwei (Nanyang Technological University, 2020)
The benefits of autonomous driving teams have gradually been realized in practical applications. First of all, vehicles on the road may not make full use of the road space to a large extent, so the throughput of highways cannot be optimized, and the use of platoon provides solutions to the problem of congestion. In addition, it provides good experiences in safety and comfortableness. The user's vehicle follows the lead vehicle, so the performance of the lead vehicle becomes the key to handling a platoon driving experience. This dissertation evaluates the performance of a method (CETVSP) that gives a reputation score to the lead vehicle to recommend the most suitable lead vehicle for potential new users in the next trip. The performance of the lead vehicle needs to be expressed by a quantitative value in order to provide an intuitive reference for potential user vehicles in the next trip. The reputation score can be significant in evaluating the performance of the lead vehicle since it integrates the feedback from all users so it can be seen as an objective assessment. The score is provided by user vehicles in a platoon, so it is obvious that the authenticity of the feedback provided by the user vehicle needs to be considered. Based on this, the abnormal behavior of user feedback is discussed and simulated in detail in the paper.The introduction of multiple attacks methods is to verify the robustness of the scheme. Furthermore, this thesis also studies the communication between vehicles by means of simulation, and obtains the influence of the number of roadside unit (RSU) module in the vehicle network on the system delay.Specifically, the results is obtained by configuring different number of RSUs and executing multiple runs under the CETVSP routing model, which results in a conclusion that the number of RSUs per unit area is inversely proportional to the delay, and the latency is from 100 to 900 µs. The routing design of simulation is based on one.